The Innovation Navigator : Transforming Your Organization in the Era of Digital Design and Collaborative Culture - Marion, Tucker J.; Fixson, Sebastian K., 1967- (Book collections on Project MUSE., 2018)
Innovation is a top strategic priority for firms across all industries. In The Innovation Navigator, Tucker J. Marion and Sebastian K. Fixson explore four innovation archetypes or modes - "specialist," "venture," "community," and "network"--Which feature prominently in the expanding innovation landscape. Specialists employ technologies to achieve entirely new solutions and superior product performance. New corporate ventures lower the barriers for employees to self-select into entrepreneurial projects, while reducing the constraints of bureaucracy. The community brings new sources of knowledge by expanding past the firm's boundaries, dramatically increasing the number of participants. The network creates partnerships and ecosystems that create innovations that could not be developed by individual companies alone. The Innovation Navigator guides the reader in exploring and exploiting these different modes of innovation. Individual chapters provide key insights into the inherent opportunities and challenges from a number of vantage points: from the impact on organizational resources to the role of incentives. The book also provides a framework for how firms can leverage dynamic mode shifts and multimode strategies. Firms across the industrial spectrum are profiled, from new additive manufacturing companies such as Formlabs, community-based solution providers like Forth, to traditional firms exploring new modes like GE Appliances and their FirstBuild initiative. The Innovation Navigator will assist executives in building the capabilities for peak performance in this new innovation landscape